High-orientation boron nitride heat-conducting gasket as well as preparation method and application thereof
Through the modification of boron nitride nanosheets and near-field electrospinning technology, a high-oriented thermal conductivity framework is formed, which solves the problems of poor out-of-plane orientation and insufficient mechanical properties of boron nitride thermal materials, and realizes high-performance thermal gaskets Preparation.
Patent Information
- Application Number
- CN202411547375.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
The existing boron nitride thermal conductivity has poor out-plane orientation, inconsistent thermal pathways, and it is difficult to maintain good mechanical properties under high boron nitride usage.
By modifying the boron nitride nanosheets with coupling agent solution, combining near-field electrospinning technology, a high-oriented boron nitride thermal skeleton is formed, and mixed with the polymer matrix solution for curing to form a high-performance thermal pad piece.
The high out-of-plane orientation and high thermal conductivity of the boron nitride thermal gasket are achieved, and good mechanical properties are maintained under high boron nitride filling amount.
Smart Images

Figure CN119410150A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermally conductive gaskets, and in particular to a highly oriented boron nitride thermally conductive gasket and a preparation method and application thereof. Background Art
[0002] As the performance of electronic devices has significantly improved, especially in computer processors, smartphones, LED lighting systems and electric vehicle power systems operating at high power, heat dissipation has become a key factor limiting device performance and reliability. Although traditional metal-based thermal conductive materials have high thermal conductivity, they are often accompanied by high density and electrical conductivity, which limits their application in some aspects.
[0003] At present, some technologies use boron nitride as a thermal conductive material, but it has at least one of the following problems: the out-of-plane orientation of boron nitride is poor and the thermal conductive path is discontinuous; the gasket made of boron nitride has a high in-plane thermal conductivity but a low out-of-plane thermal conductivity; the gasket made of boron nitride is difficult to maintain good mechanical properties at a higher boron nitride dosage.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a highly oriented boron nitride thermally conductive pad and a preparation method and application thereof, so as to solve or improve the above-mentioned technical problems.
[0006] The present invention can be implemented like this:
[0007] In a first aspect, the present invention provides a method for preparing a highly oriented boron nitride thermally conductive pad, comprising the following steps:
[0008] The boron nitride nanosheets are modified by using a coupling agent solution to obtain modified boron nitride nanosheets;
[0009] The modified boron nitride nanosheets are mixed with a polyacrylonitrile solution to obtain a spinning slurry;
[0010] The spinning slurry is subjected to near-field electrospinning to obtain a fiber sheet;
[0011] The fiber sheet is pre-oxidized and then carbonized under a protective atmosphere to obtain a thermally conductive skeleton;
[0012] The thermally conductive skeleton is mixed with the polymer matrix solution so that the polymer matrix solution is impregnated into the thermally conductive skeleton, followed by curing.
[0013] In an optional embodiment, modifying the boron nitride nanosheets with a coupling agent solution includes: adding the boron nitride nanosheets to the coupling agent solution and performing ultrasonic dispersion.
[0014] In an optional embodiment, the coupling agent in the coupling agent solution is a silane coupling agent.
[0015] In an alternative embodiment, the silane coupling agent includes KH570 coupling agent.
[0016] In an alternative embodiment, the solvent in the coupling agent solution includes ethanol and water.
[0017] In an optional embodiment, the solid content of the coupling agent solution is 0.5 wt % to 5 wt %.
[0018] In an optional embodiment, the boron nitride nanosheets have a diameter of 50 nm to 100 nm.
[0019] In an optional embodiment, the mass ratio of the modified boron nitride nanosheets to the polyacrylonitrile contained in the polyacrylonitrile solution is 10:1 to 3:1.
[0020] In an optional embodiment, the mass concentration of polyacrylonitrile in the polyacrylonitrile solution is 5 wt % to 15 wt %.
[0021] In an alternative embodiment, the solvent in the polyacrylonitrile solution includes N,N-dimethylformamide.
[0022] In an optional embodiment, the liquid supply rate of near-field electrospinning is 0.2 mL / h to 0.5 mL / h, the distance between the needle and the receiver is 0.5 mm to 5 mm, the voltage is 1 kV to 5 kV, and the horizontal displacement speed of the receiver is 5 cm / s to 10 cm / s.
[0023] In an optional embodiment, the pre-oxidation is carried out at 350° C. to 380° C. for 1.5 h to 2 h.
[0024] In an optional embodiment, the carbonization is carried out at 700° C. to 1100° C. for 1.5 h to 3 h.
[0025] In an optional embodiment, the polymer matrix in the polymer matrix solution includes at least one of organic silica gel, epoxy resin, acrylate, polyimide and natural rubber.
[0026] In a second aspect, the present invention provides a highly oriented boron nitride thermally conductive gasket prepared by the preparation method of any one of the aforementioned embodiments.
[0027] In an optional embodiment, the mass percentage of the thermally conductive skeleton in the highly oriented boron nitride thermally conductive gasket is 30% to 70%;
[0028] And / or, the thickness of the highly oriented boron nitride thermally conductive gasket is 0.5 mm to 2 mm.
[0029] In a third aspect, the present invention provides an electronic device comprising the highly oriented boron nitride thermally conductive gasket of the aforementioned embodiment.
[0030] The beneficial effects of the present invention include:
[0031] In the preparation method of the thermally conductive gasket provided by the present invention, the dispersibility of the flake boron nitride in the polyacrylonitrile solution can be improved by coupling agent modification, so that the polyacrylonitrile solution is more easily adsorbed on the interface connection of the boron nitride nanosheet, which lays the foundation for the subsequent formation of carbonized welding at the interface and reducing the interface thermal resistance. The near-field electrostatic spinning technology is used to not only realize the radial orientation of the boron nitride nanosheet along the nanofiber, but also to arrange each layer of nanofibers in parallel and regularly in the plane. This orderly arrangement allows a more compact and continuous heat conduction channel to be formed between the thermally conductive fillers. After vertical cutting, the composite thermally conductive gasket has excellent out-of-plane orientation and high out-of-plane thermal conductivity. In addition, the formation of the interface is also avoided by the layer-by-layer spinning method, reducing the interface thermal resistance. Further, by infiltrating the high molecular weight polyacrylonitrile between the interfaces of the boron nitride nanosheets, a special thermally conductive skeleton of carbon fiber-coated boron nitride is formed after spinning carbonization treatment. This structure greatly reduces the thermal resistance between the boron nitrides, forming a truly interconnected and connected thermally conductive network, which is more conducive to the preparation of high-performance thermal interface materials compared to other forms of boron nitride thermal conductive network structures. In addition, the coating effect of carbon fiber can enhance the mechanical properties of the thermal conductive gasket, making it easy to achieve ultra-high content of boron nitride filling, ensuring that the gasket has excellent thermal conductivity.
[0032] That is, the preparation method of the thermally conductive gasket provided by the present invention is simple to operate, and can make the boron nitride maintain good orientation in the thermally conductive gasket, so that the thermally conductive gasket has a highly connected thermal conductive path, and thus can have excellent thermal conductivity in the out-of-plane orientation. The boron nitride thermally conductive gasket prepared in this way can maintain a high out-of-plane thermal conductivity and good mechanical properties under the condition of a high boron nitride filling amount. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 A process flow chart of a method for preparing a highly oriented boron nitride thermally conductive pad provided by the present invention;
[0035] Figure 2 is a schematic diagram of the structure of the fiber sheet in Example 1 of the present invention;
[0036] Figure 3 This is a schematic diagram of the structure of the heat-conducting skeleton in Example 1 of the present invention;
[0037] Figure 4 This is a cross-sectional view of the highly oriented boron nitride thermally conductive gasket provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0039] The highly oriented boron nitride thermal conductive gasket provided by the present invention and its preparation method and application are described in detail below.
[0040] The present invention provides a method for preparing a highly oriented boron nitride thermally conductive pad. Figure 1 , including the following steps:
[0041] S1: modifying the boron nitride nanosheets using a coupling agent solution to obtain modified boron nitride nanosheets.
[0042] In some optional embodiments, the diameter of the boron nitride nanosheets can be 50nm to 100nm, such as 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm or 100nm, etc., or other values within the range of 50nm to 100nm. In other optional embodiments, boron nitride nanosheets with other diameters are not excluded.
[0043] In some optional embodiments, modifying the boron nitride nanosheets with a coupling agent solution may include: adding the boron nitride nanosheets to the coupling agent solution and performing ultrasonic dispersion.
[0044] In some specific embodiments, the coupling agent and the solvent are first mixed, and then the boron nitride nanosheets are added to obtain a mixed solution. The pH value of the mixed solution is adjusted to 3.5-4.5, and ultrasonic dispersion is performed.
[0045] In some optional embodiments, the mass ratio of boron nitride nanosheets to the coupling agent in the coupling agent solution can be 100:4 to 100:6, such as 100:4, 100:4.5, 100:5, 100:5.5 or 100:6, or other values within the range of 100:4 to 100:6.
[0046] The coupling agent in the coupling agent solution may be a silane coupling agent, such as KH570 coupling agent, etc. In addition, the coupling agent in the coupling agent solution may also be a non-silane coupling agent.
[0047] The solvent in the coupling agent solution includes ethanol and water, and the volume ratio of ethanol to water can be, for example, 3:1.
[0048] The solid content of the coupling agent solution can be 0.5wt% to 5wt%, such as 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc., or other values within the range of 0.5wt% to 5wt%.
[0049] The pH value of the mixed solution can be adjusted by using reagents such as acetic acid. The above pH value adjustment can effectively control the hydrolysis rate and reduce the self-polymerization reaction between silane coupling agent molecules, thereby obtaining a more stable hydrolysis solution. If the pH value is too low, the hydrolysis reaction may be excessively promoted, resulting in the silane coupling agent being hydrolyzed too quickly and generating too much silanol, which may cause the silane coupling agent to self-polymerize or gel, thereby affecting its uniform distribution on the substrate surface and the coupling effect; if the pH value is too high, the hydrolysis rate of the silane coupling agent may be reduced, resulting in a decrease in its activity, thereby affecting its performance and stability.
[0050] The ultrasonic dispersion time may be illustratively but not limited to 1 h to 2 h.
[0051] Furthermore, after ultrasonic dispersion, the product can be stirred at room temperature for 24 hours using a magnetic stirrer, and the product can be centrifuged and washed with anhydrous ethanol (e.g., the centrifugal speed can be 3500 r / min, and the centrifugal time can be 5 minutes each time). The solid obtained by washing is dried (e.g., dried in a vacuum drying oven at 80° C. for 24 hours) to obtain modified boron nitride nanosheets.
[0052] As mentioned above, by modifying the boron nitride nanosheets with a coupling agent solution, the mixing uniformity of the boron nitride nanosheets and the polyacrylonitrile solution can be improved to obtain a uniform spinning slurry.
[0053] S2: Mixing the modified boron nitride nanosheets with the polyacrylonitrile solution to obtain a spinning slurry.
[0054] The polyacrylonitrile in the polyacrylonitrile solution is used to form carbon fibers.
[0055] In some optional embodiments, the mass ratio of modified boron nitride nanosheets to polyacrylonitrile contained in the polyacrylonitrile solution is 10:1 to 3:1, such as 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1 or 3:1, or other values within the range of 10:1 to 3:1.
[0056] If the mass ratio of the modified boron nitride nanosheets and the polyacrylonitrile contained in the polyacrylonitrile solution is relatively low (such as 2:1), the spun fibers will be discontinuous, the fiber beads will be too large, the diameter will be too small, etc., which will cause the mechanical properties of the gasket (such as tensile strength) to deteriorate; if the mass ratio of the modified boron nitride nanosheets and the polyacrylonitrile contained in the polyacrylonitrile solution is relatively high (such as 12:1), the thermal resistance will increase, resulting in poor thermal conductivity of the gasket.
[0057] In some optional embodiments, the mass concentration of polyacrylonitrile in the polyacrylonitrile solution can be 5wt% to 15wt%, such as 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%, etc., or it can be other values within the range of 5wt% to 15wt%.
[0058] In some optional embodiments, the solvent in the polyacrylonitrile solution may illustratively but not limitatively include N,N-dimethylformamide and the like.
[0059] In some optional embodiments, the modified boron nitride nanosheets and the polyacrylonitrile solution may be mixed and stirred at a constant temperature of 55° C. to 65° C. for 1.5 h to 3 h.
[0060] S3: The spinning slurry is subjected to near-field electrospinning to obtain a fiber sheet.
[0061] The spinning path can be controlled by the receiver's rapid reciprocating displacement along the X-axis and superimposed layer by layer.
[0062] In some optional embodiments, the liquid supply rate of near-field electrospinning can be 0.2 mL / h to 0.5 mL / h, such as 0.2 mL / h, 0.25 mL / h, 0.3 mL / h, 0.35 mL / h, 0.4 mL / h, 0.45 mL / h or 0.5 mL / h, etc., or other values within the range of 0.2 mL / h to 0.5 mL / h.
[0063] The distance between the needle and the receiver can be 0.5mm to 5mm, such as 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm or 5mm, or other values within the range of 0.5mm to 5mm.
[0064] The horizontal displacement speed of the receiver can be 5cm / s to 10cm / s, such as 5cm / s, 5.5cm / s, 6cm / s, 6.5cm / s, 7cm / s, 7.5cm / s, 8cm / s, 8.5cm / s, 9cm / s, 9.5cm / s or 10cm / s, etc., or it can be other values within the range of 5cm / s to 10cm / s.
[0065] The needle gauge may be, by way of example but not limitation, 30G, 32G or 34G.
[0066] The voltage may be 1 kV to 5 kV, such as 1 kV, 1.5 kV, 2 kV, 2.5 kV, 3 kV, 3.5 kV, 4 kV, 4.5 kV or 5 kV, or other values within the range of 1 kV to 5 kV.
[0067] The thickness of the fiber sheet obtained by spinning can be 1 cm to 2 cm.
[0068] It should be noted that the conventional electrospinning method produces spiral fibers, with large interface thermal resistance and poor thermal conductivity. The present invention sets the liquid supply speed, the distance between the needle and the receiver, the horizontal displacement speed of the receiver and the voltage in a specific range and cooperates with each other, so that the prepared fibers are linear, which is conducive to obtaining an interface with good adhesion, thereby reducing the interface thermal resistance and improving the thermal conductivity.
[0069] S4: pre-oxidizing the fiber sheet and then carbonizing it under a protective atmosphere to obtain a thermally conductive skeleton.
[0070] The above-mentioned pre-oxidation can be carried out at 250°C to 350°C for 1.5h to 2h.
[0071] The pre-oxidation temperature may be 250°C, 255°C, 260°C, 265°C, 270°C, 275°C or 280°C, or other values within the range of 250°C to 350°C.
[0072] If the pre-oxidation temperature is lower than 250°C (such as 180°C or 200°C), the diffusion rate of oxygen is lower than the cyclization reaction rate, which may lead to insufficient pre-oxidation, thus affecting the density and mechanical properties of the carbon fiber. If the pre-oxidation temperature is too high (such as 400°C), the oxygen content will increase sharply, and it will be difficult for the fiber to form a cyclization structure, which may lead to the aggravation of the skin-core structure of the pre-oxidized fiber, affecting the uniformity and mechanical properties of the carbon fiber.
[0073] The pre-oxidation holding time may be 1.5 h, 1.8 h or 2 h, etc., or may be other values within the range of 1.5 h to 2 h.
[0074] The heating rate during the pre-oxidation process can be 4°C / min to 6°C / min, such as 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min or 6°C / min, or other values within the range of 4°C / min to 6°C / min.
[0075] By pre-oxidation, the non-carbon elements in polyacrylonitrile are converted into oxygen-containing compounds to improve the carbonization effect.
[0076] The carbonization can be carried out at 700°C to 1100°C for 1.5h to 3h.
[0077] The carbonization temperature may be 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C or 1100°C, or other values within the range of 700°C to 1100°C.
[0078] The carbonization time may be 1.5 h, 2 h, 2.5 h or 3 h, or other values within the range of 1.5 h to 3 h.
[0079] The heating rate during the carbonization process can be 4°C / min to 6°C / min, such as 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min or 6°C / min, or other values within the range of 4°C / min to 6°C / min.
[0080] The protective atmosphere may be, for example, an argon atmosphere.
[0081] Through carbonization, polyacrylonitrile is transformed into carbon fibers with high orientation.
[0082] S5: mixing the thermally conductive skeleton with the polymer matrix solution so that the polymer matrix solution is impregnated into the thermally conductive skeleton, followed by curing.
[0083] In some optional embodiments, the thermally conductive skeleton can be placed in a mold, a certain amount of polymer matrix solution can be poured into it, the polymer matrix can be immersed in the thermally conductive skeleton by vacuuming, and the thermally conductive skeleton immersed in the polymer matrix can be taken out for curing. After curing, the cured product can be cut into slices of a certain thickness along a direction perpendicular to the X-axis as needed.
[0084] In some optional embodiments, the polymer matrix in the polymer matrix solution may illustratively but not limitatively include at least one of organic silicone, epoxy resin, acrylate, polyimide and natural rubber.
[0085] In some optional embodiments, the dosage relationship between the thermally conductive skeleton and the polymer matrix solution can be set according to the mass percentage of the thermally conductive skeleton in the cured product being 30% to 70% (such as 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, etc.).
[0086] The curing temperature and time can be set accordingly according to the polymer matrix used.
[0087] In some optional embodiments, the thickness of the slice after cutting may be 0.5 mm to 2 mm, such as 0.5 mm, 1 mm, 1.5 mm or 2 mm.
[0088] As mentioned above, in the preparation method of the thermally conductive gasket provided by the present invention, the dispersibility of boron nitride in the polyacrylonitrile solution can be improved by coupling agent modification, so that the polyacrylonitrile solution is more easily adsorbed on the interface connection of the boron nitride nanosheets, which lays the foundation for the subsequent formation of carbonization welding at the interface (during the carbonization process, the interface bonding between the PAN matrix and the BN nanosheets will be enhanced, and this bonding may be achieved through physical entanglement, van der Waals forces, or chemical bonds formed at the interface. This bonding process is referred to as welding here) and reducing the interface thermal resistance. The near-field electrospinning technology is used to not only achieve the radial orientation of the boron nitride nanosheets along the nanofibers, but also to arrange each layer of nanofibers in parallel and regularly in the plane. This orderly arrangement allows the thermal conductive fillers to form a more compact and continuous heat conduction channel. After vertical cutting, the composite thermally conductive gasket has excellent out-of-plane orientation and high out-of-plane thermal conductivity. In addition, the formation of the interface is avoided by the layer-by-layer spinning method, which reduces the interface thermal resistance. Furthermore, by infiltrating the high molecular weight polyacrylonitrile between the interfaces of the boron nitride nanosheets, a special thermal conductive skeleton of carbon fiber coated boron nitride is formed after spinning and carbonization. This structure greatly reduces the thermal resistance between boron nitrides and forms a real interconnected thermal conductive network. Compared with other forms of boron nitride thermal conductive network structures, it is more conducive to the preparation of high-performance thermal interface materials. In addition, the coating effect of carbon fiber can enhance the mechanical properties of the thermal conductive gasket, making it easy to achieve ultra-high content of boron nitride filling, ensuring that the gasket has excellent thermal conductivity.
[0089] Correspondingly, the present invention also provides a highly oriented boron nitride thermally conductive gasket, which is prepared by the above-mentioned preparation method.
[0090] The mass percentage of the heat-conducting skeleton in the high-oriented boron nitride heat-conducting pad is 30% to 70%, and the thickness of the high-oriented boron nitride heat-conducting pad is 0.5 mm to 2 mm.
[0091] The highly oriented boron nitride thermally conductive gasket has the characteristics of high out-of-plane orientation and high thermal conductivity. In addition, the highly oriented boron nitride thermally conductive gasket can have high mechanical properties (such as tensile strength) under the premise of high boron nitride filling amount.
[0092] In addition, the present invention also provides an electronic device, which contains the above-mentioned high-oriented boron nitride thermal conductive pad to have higher heat dissipation performance.
[0093] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0094] Example 1
[0095] This embodiment provides a highly oriented boron nitride thermally conductive pad, the preparation method of which includes:
[0096] S1: Preparation of modified boron nitride nanosheets.
[0097] KH570 silane coupling agent was added to a mixture of anhydrous ethanol and deionized water, and then boron nitride nanosheets were added to obtain a mixed solution. The pH value of the mixed solution was adjusted to 4.0 with acetic acid, and after ultrasonic dispersion for 1 hour, it was stirred at room temperature for 24 hours with a magnetic stirrer, and the product was centrifugally washed 4 times with anhydrous ethanol (the centrifugal speed was 3500r / min, and each centrifugation was 5 minutes). The solid obtained by washing was dried in a vacuum drying oven at 80°C for 24 hours to obtain modified boron nitride nanosheets.
[0098] The diameter of the boron nitride nanosheets is 50nm-100nm; the mass ratio of the boron nitride nanosheets to KH570 is 100:4; the solid content of the coupling agent solution is 0.6wt%; and the volume ratio of deionized water to anhydrous ethanol in the mixed solution is 1:3.
[0099] S2: preparing spinning slurry.
[0100] Weigh polyacrylonitrile powder and add it to N,N-dimethylformamide, heat and stir to dissolve the polyacrylonitrile powder to obtain a polyacrylonitrile solution with a concentration of 11wt%. Then, according to the mass ratio of modified boron nitride nanosheets to polyacrylonitrile of 3:1, add the modified boron nitride nanosheets to the polyacrylonitrile solution, heat it to 60°C, and stir it at a constant temperature in a magnetic stirrer for 2h to obtain a spinning slurry.
[0101] S3: Preparation of fiber sheets (such as Figure 2 shown).
[0102] The spinning slurry was subjected to near-field electrospinning, wherein the automatic liquid supply speed of the injection pump during electrospinning was 0.3 mL / h, the distance between the needle and the receiver was 2 mm, the applied voltage was 2 kV, the horizontal displacement speed of the receiver was 8 cm / s, the spinning needle was a 34G stainless steel needle, and near-field electrospinning was performed according to the route set by the computer, and spinning was performed layer by layer until the thickness of the fiber sheet reached 2 cm.
[0103] S4: Preparation of thermally conductive skeleton (such as Figure 3 shown).
[0104] The fiber sheet was placed in a muffle furnace, heated to 300°C at a heating rate of 5°C / min and kept warm for 1.5 hours for pre-oxidation; the pre-oxidized fiber sheet was then placed in a tubular furnace, heated to 1000°C at a heating rate of 5°C / min in an argon atmosphere and carbonized for 2 hours. After cooling, the sample was taken out to obtain a highly oriented thermally conductive skeleton.
[0105] S5: Prepare a highly oriented boron nitride thermally conductive gasket.
[0106] The thermally conductive skeleton was placed in a mold, and organic silica gel was added. The mold was evacuated for 2 hours to allow the organic silica gel to be completely immersed in the thermally conductive skeleton. The mold was cured at 120°C for 2 hours. After curing, the mold was cut into 0.5 mm thick slices along the vertical direction to obtain a highly out-of-plane oriented boron nitride thermally conductive gasket, in which the content of the thermally conductive skeleton was 60wt%.
[0107] The cross-sectional view of the highly oriented boron nitride thermally conductive pad obtained in this embodiment is as follows: Figure 4 As shown, it can be seen from the figure that boron nitride is interspersed in the carbon fiber network (it can also be understood that the carbon fiber network wraps the boron nitride) and has good out-of-plane orientation.
[0108] Example 2
[0109] The difference between this embodiment and embodiment 1 is that the mass ratio of the modified boron nitride nanosheets to polyacrylonitrile is 5:1.
[0110] Example 3
[0111] The difference between this embodiment and embodiment 1 is that the mass ratio of the modified boron nitride nanosheets to polyacrylonitrile is 7:1.
[0112] Example 4
[0113] This embodiment provides a highly oriented boron nitride thermally conductive pad, the preparation method of which includes:
[0114] S1: Preparation of modified boron nitride nanosheets.
[0115] KH570 silane coupling agent was added to a mixture of anhydrous ethanol and deionized water, and then boron nitride nanosheets were added to obtain a mixed solution. The pH value of the mixed solution was adjusted to 4 with acetic acid, and after ultrasonic dispersion for 1.5 hours, it was stirred at room temperature for 24 hours with a magnetic stirrer, and the product was centrifugally washed 3 times with anhydrous ethanol (the centrifugal speed was 3500r / min, and each centrifugation was 5 minutes). The solid obtained by washing was dried in a vacuum drying oven at 80°C for 24 hours to obtain modified boron nitride nanosheets.
[0116] The diameter of the boron nitride nanosheets is 50nm-100nm; the mass ratio of the boron nitride nanosheets to KH570 is 100:5; the solid content of the coupling agent solution is 2wt%; and the volume ratio of deionized water to anhydrous ethanol in the mixed solution is 1:3.
[0117] S2: preparing spinning slurry.
[0118] Weigh polyacrylonitrile powder and add it to N,N-dimethylformamide, heat and stir to dissolve the polyacrylonitrile powder to obtain a polyacrylonitrile solution with a concentration of 12wt%. Then, according to the mass ratio of modified boron nitride nanosheets to polyacrylonitrile of 3:1, add the modified boron nitride nanosheets to the polyacrylonitrile solution, heat it to 55°C, and stir it at a constant temperature in a magnetic stirrer for 3h to obtain a spinning slurry.
[0119] S3: preparing a fiber sheet.
[0120] The spinning slurry was subjected to near-field electrospinning, wherein the automatic liquid supply speed of the injection pump during electrospinning was 0.2 mL / h, the distance between the needle and the receiver was 0.5 mm, the applied voltage was 1 kV, the horizontal displacement speed of the receiver was 5 cm / s, the spinning needle was a 30G stainless steel needle, and near-field electrospinning was performed according to the route set by the computer, and spinning was performed layer by layer until the thickness of the fiber sheet reached 1 cm.
[0121] S4: Prepare a thermally conductive skeleton.
[0122] The fiber sheet was placed in a muffle furnace, heated to 350°C at a heating rate of 4°C / min and kept warm for 2 hours for pre-oxidation; the pre-oxidized fiber sheet was then placed in a tubular furnace, heated to 700°C at a heating rate of 4°C / min in an argon atmosphere and carbonized for 3 hours. After cooling, the sample was taken out to obtain a highly oriented thermally conductive skeleton.
[0123] S5: Prepare a highly oriented boron nitride thermally conductive gasket.
[0124] Put the thermally conductive skeleton into the mold, add epoxy resin, evacuate for 2 hours to allow the epoxy resin to completely penetrate into the thermally conductive skeleton, cure at 180°C for 2 hours, and cut into 0.5 mm thick slices along the vertical direction after curing to obtain a highly out-of-plane oriented boron nitride thermally conductive gasket, in which the content of the thermally conductive skeleton is 50wt%.
[0125] Example 5
[0126] This embodiment provides a highly oriented boron nitride thermally conductive pad, the preparation method of which includes:
[0127] S1: Preparation of modified boron nitride nanosheets.
[0128] KH570 silane coupling agent was added to a mixture of anhydrous ethanol and deionized water, and then boron nitride nanosheets were added to obtain a mixed solution. The pH value of the mixed solution was adjusted to 4 with acetic acid, and after ultrasonic dispersion for 2 hours, it was stirred at room temperature for 24 hours with a magnetic stirrer, and the product was centrifugally washed 4 times with anhydrous ethanol (the centrifugal speed was 3500r / min, and each centrifugation was 5 minutes). The solid obtained by washing was dried in a vacuum drying oven at 80°C for 24 hours to obtain modified boron nitride nanosheets.
[0129] The diameter of the boron nitride nanosheets is 50nm-100nm; the mass ratio of the boron nitride nanosheets to KH570 is 100:6; the solid content of the coupling agent solution is 5wt%; and the volume ratio of deionized water to anhydrous ethanol in the mixed solution is 1:3.
[0130] S2: preparing spinning slurry.
[0131] Weigh polyacrylonitrile powder and add it to N,N-dimethylformamide, heat and stir to dissolve the polyacrylonitrile powder to obtain a polyacrylonitrile solution with a concentration of 15wt%. Then, according to the mass ratio of modified boron nitride nanosheets to polyacrylonitrile of 10:1, add the modified boron nitride nanosheets to the polyacrylonitrile solution, heat it to 65°C, and stir it at a constant temperature in a magnetic stirrer for 1.5 hours to obtain a spinning slurry.
[0132] S3: preparing a fiber sheet.
[0133] The spinning slurry was subjected to near-field electrospinning, wherein the automatic liquid supply speed of the injection pump during electrospinning was 0.5 mL / h, the distance between the needle and the receiver was 5 mm, the applied voltage was 5 kV, the horizontal displacement speed of the receiver was 10 cm / s, the spinning needle was a 32G stainless steel needle, and near-field electrospinning was performed according to the route set by the computer, and spinning was performed layer by layer until the thickness of the fiber sheet reached 1.5 cm.
[0134] S4: Prepare a thermally conductive skeleton.
[0135] The fiber sheet was placed in a muffle furnace, heated to 280°C at a heating rate of 6°C / min and kept warm for 1.5 hours for pre-oxidation; the pre-oxidized fiber sheet was then placed in a tubular furnace, heated to 1100°C at a heating rate of 6°C / min in an argon atmosphere and carbonized for 1.5 hours. After cooling, the sample was taken out to obtain a highly oriented thermally conductive skeleton.
[0136] S5: Prepare a highly oriented boron nitride thermally conductive gasket.
[0137] The thermally conductive skeleton was placed in a mold, and acrylic resin was added. The mold was vacuumed for 2 hours to allow the natural rubber to be completely immersed in the thermally conductive skeleton. The mold was cured at 100°C for 2 hours. After curing, the mold was cut into 0.5 mm thick slices along the vertical direction to obtain a highly out-of-plane oriented boron nitride thermally conductive gasket, in which the content of the thermally conductive skeleton was 70wt%.
[0138] Comparative Example 1
[0139] This comparative example is a pure organic silicone gasket.
[0140] Comparative Example 2
[0141] The difference between this comparative example and Example 1 is that the spinning slurry obtained in S2 is not subjected to the spinning operation of S3, but the spinning solution is subjected to vacuum filtration. After the filtration, a polyacrylonitrile / boron nitride cake is obtained, which is placed in a blast drying oven and dried at 50°C for 12 hours, and then prepared into a thermally conductive skeleton through the operation of S4, and finally prepared into a thermally conductive gasket according to S5.
[0142] Comparative Example 3
[0143] The difference between this comparative example and Example 1 is that the fiber sheet obtained in S3 is not subjected to the operation in S4, but is directly prepared into a thermal conductive pad according to the method in S5.
[0144] That is, the thermal conductive gasket of this comparative example does not contain carbon fiber wrapped with boron nitride, but contains polyacrylonitrile fiber wrapped with boron nitride.
[0145] Comparative Example 4
[0146] The difference between this comparative example and Example 1 is that S1 is not performed, and the boron nitride nanosheets are directly mixed with the polyacrylonitrile solution according to the method of S2 to prepare the spinning slurry. The remaining steps are the same as in Example 1.
[0147] Comparative Example 5
[0148] The difference between this comparative example and Example 1 is that in S2, the mass ratio of the modified boron nitride nanosheets to the polyacrylonitrile contained in the polyacrylonitrile solution is 2:1. The remaining steps are the same as in Example 1.
[0149] Comparative Example 6
[0150] The difference between this comparative example and Example 1 is that in S3, the liquid supply rate of near-field electrospinning is 1 mL / h. The remaining steps are the same as in Example 1.
[0151] Comparative Example 7
[0152] The difference between this comparative example and Example 1 is that in S3, the distance between the needle and the receiver is 8 mm. The remaining steps are the same as in Example 1.
[0153] Comparative Example 8
[0154] The difference between this comparative example and Example 1 is that in S3, the voltage is 8 kV. The remaining steps are the same as in Example 1.
[0155] Comparative Example 9
[0156] The difference between this comparative example and Example 1 is that in S3, the horizontal displacement speed of the receiver is 12 cm / s. The remaining steps are the same as those in Example 1.
[0157] Comparative Example 10
[0158] The difference between this comparative example and Example 1 is that in S3, the horizontal displacement speed of the receiver is 1 cm / s. The remaining steps are the same as those in Example 1.
[0159] Test example
[0160] The thermally conductive pads provided in Examples 1 to 5 and Comparative Examples 1 to 10 were subjected to performance tests.
[0161] The out-of-plane thermal conductivity of the thermally conductive gasket was tested according to the flash method of American standard ASTM E1461, and the tensile strength of the thermally conductive gasket was tested according to ASTMD3039, and the results are shown in Table 1. The above-mentioned "out-of-plane thermal conductivity" refers to the thermal conductivity in the vertical direction of the sheet layer.
[0162] Table 1 Test results
[0163]
[0164]
[0165] It can be seen from Table 1 that, compared with the pure organic silicone gasket provided in Comparative Example 1, the thermally conductive gaskets provided in Examples 1 to 5 of the present invention can have both higher out-of-plane thermal conductivity and higher tensile strength under the condition of a higher filling amount of flaky boron nitride.
[0166] By comparing Example 1 with Comparative Examples 2 and 3, it can be seen that the out-of-plane thermal conductivity of the thermally conductive gasket can be significantly improved by first spinning the spinning slurry and then preparing it into a thermally conductive skeleton and then preparing it into a thermally conductive gasket.
[0167] By comparing Example 1 with Comparative Examples 4 to 10, it can be seen that if some conditions are improperly set during the preparation process, it will also make it difficult for the thermally conductive gasket to have both high out-of-plane thermal conductivity and high tensile strength under the condition of a high filling amount of flaky boron nitride.
[0168] In summary, the preparation method of the thermally conductive gasket provided by the present invention is simple to operate, can make the boron nitride maintain good orientation in the thermally conductive gasket, make the thermally conductive gasket have a highly connected heat conduction path, and thus can have excellent thermal conductivity in the out-of-plane orientation. The boron nitride thermally conductive gasket prepared in this way can maintain a high out-of-plane thermal conductivity and good mechanical properties under the condition of a high boron nitride filling amount.
[0169] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a highly oriented boron nitride thermally conductive pad, characterized in that: The following steps are involved: The boron nitride nanosheets are modified by using a coupling agent solution to obtain modified boron nitride nanosheets; Mixing the modified boron nitride nanosheets with a polyacrylonitrile solution to obtain a spinning slurry; The spinning slurry is subjected to near-field electrospinning to obtain a fiber sheet; Pre-oxidizing the fiber sheet, and then carbonizing it under a protective atmosphere to obtain a thermally conductive skeleton; The thermally conductive skeleton is mixed with a polymer matrix solution so that the polymer matrix solution is impregnated into the thermally conductive skeleton, followed by curing.
2. The preparation method according to claim 1, characterized in that: Modifying the boron nitride nanosheets with the coupling agent solution includes: adding the boron nitride nanosheets into the coupling agent solution and performing ultrasonic dispersion; Preferably, the mass ratio of the boron nitride nanosheets to the coupling agent in the coupling agent solution is 100:4 to 100:6; Preferably, the coupling agent in the coupling agent solution is a silane coupling agent; Preferably, the silane coupling agent includes KH570 coupling agent; Preferably, the solvent in the coupling agent solution includes ethanol and water; Preferably, the solid content of the coupling agent solution is 0.5wt% to 5wt%; Preferably, the boron nitride nanosheets have a sheet diameter of 50 nm to 100 nm.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the modified boron nitride nanosheets to the polyacrylonitrile contained in the polyacrylonitrile solution is 10:1 to 3:1; Preferably, the mass concentration of polyacrylonitrile in the polyacrylonitrile solution is 5wt% to 15wt%; Preferably, the solvent in the polyacrylonitrile solution includes N,N-dimethylformamide.
4. The preparation method according to claim 1, characterized in that: The liquid supply rate of near-field electrospinning is 0.2mL / h~0.5mL / h, the distance between the needle and the receiver is 0.5mm~5mm, the voltage is 1kV~5kV, and the horizontal displacement speed of the receiver is 5cm / s~10cm / s.
5. The preparation method according to claim 1, characterized in that: The pre-oxidation is carried out at 350°C to 380°C for 1.5h to 2h.
6. The preparation method according to claim 1, characterized in that: The carbonization is carried out at 700°C to 1100°C for 1.5h to 3h.
7. The preparation method according to claim 1, characterized in that: The polymer matrix in the polymer matrix solution includes at least one of organic silica gel, epoxy resin, acrylate, polyimide and natural rubber.
8. A highly oriented boron nitride thermally conductive pad, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. The highly oriented boron nitride thermally conductive gasket according to claim 8, characterized in that: The mass percentage of the thermally conductive skeleton in the highly oriented boron nitride thermally conductive gasket is 30% to 70%; And / or, the thickness of the highly oriented boron nitride thermally conductive gasket is 0.5 mm to 2 mm.
10. An electronic device, characterized in that: The electronic device contains the highly oriented boron nitride thermally conductive gasket according to claim 8 or 9.